Islamically oriented humanitarian NGOs in Turkey: AKP foreign policy parallelism. (2nd July 2016) - Çelik, Nihat; İşeri, Emre
ABSTRACT: This paper aims to contribute to the growing Foreign Policy Analysis literature by focusing on the role of non-state actors in foreign policy implementation. Special attention is paid to the case of Turkey, which has emerged as a 'humanitarian state' in the last decade. In Turkey, relatively new Islamically oriented humanitarian NGOs (HNGOs) have been providing ever-increasing amounts of humanitarian aid throughout the former Ottoman lands including the Middle East and Africa. Employing a constructivist-realist perspective, this paper asserts that a 'parallelism, ' if not a complementarity, exists between Turkey's Islamically oriented HNGO discourse and practice and AKP foreign policy implementation process. Based on primary qualitative data acquired from interviews, this study has identified various degrees of parallelism between the two, calling into question the status of these HNGOs as purportedly non-governmental entities.